A POST-PROCESS APPROACH: E-MAIL DIALOGUE JOURNAL WRITING AND ITS IMPACT ON QUALITY AND QUANTITY OF HIGH SCHOOL STUDENTS' WRITING - Malihe Rezaei; Elham Manzari (Universitas Katolik Indonesia Atma Jaya, 2011)
E-mail Dialogue Journal Writing as a form of post-process approach provides students with the opportunity to communicate and collaborate with a native speaker, thus, receive authentic language input which develops their literacy skills. Despite its remarkable potentials, E-DJW practices have been rare in Asian contexts at school-level. In an attempt to bridge this gap, the present study was set out to address the impact of E-DJW on the quality and quantity of students' writing development. The findings of the study revealed that there was a lot of topic extension between the parties in the dialogue journal writing activity and the content of the writings was principally improved. A progress was also observed in the length of the entries, though not steadily. This study hopes to raise both students' and teachers' awareness of E-DJW as a writing activity which provides students with a non-threatening environment which fosters learning and makes them aware of the purpose of writing. Keywords: E-mail Dialogue Journal Writing (E-DJW), writing quality, writing quantity, post-process approach